Effect of small-quantity lipid-based nutrient supplements on growth, psychomotor development, iron status, and morbidity among 6- to 12-mo-old infants in South Africa: A randomized controlled trial - Smuts, Corneluis M.; Matsungo, Tonderayi M.; Malan, Linda; Kruger, Hernulina S.; Rothman, Marinel; Covic, Namukolo (American Society for Nutrition, 2019)
Background Evidence on the effect of small-quantity lipid-based nutrient supplements (SQ-LNSs) on early child growth and development is mixed. Objective This study assessed the effect of daily consumption of 2 different SQ-LNS formulations on linear growth (primary outcome), psychomotor development, iron status (secondary outcomes), and morbidity in infants from age 6 to 12 mo within the context of a maize-based complementary diet.